Aiming to deceive: examining the role of the quiet eye during deceptive aiming actions - Wood, G.; Vine, S. J.; Parr, J.; Wilson, M. R. (Journal of Sport & Exercise Psychology, 2017)
In three experiments, we explored the use of deceptive gaze in soccer penalty takers using eye-tracking equipment. In Experiment 1, players competed against a goalkeeper while taking unconstrained shots. Results indicated that when players used deception (looking to the opposite side to which they shot), they extended the duration of their final aiming (quiet eye) fixation and maintained shooting accuracy. In Experiment 2, with no goalkeeper present, players still used extended quiet-eye durations when using a deceptive strategy, but this time, their accuracy suffered. In Experiment 3, we manipulated the goalkeeper`s location while controlling for the use of peripheral vision and memory of goal size. Results indicated that increased quiet-eye durations were required when using deceptive aiming, and that accuracy was influenced by the position of the goalkeeper. We conclude that during deceptive aiming, soccer players maintain accuracy by covertly processing information related to the goalkeeper`s location.